Religion and internet - Enstedt, Daniel.; Larsson, Göran.; Pace, Enzo. (Annual Review of the Sociology of Religion, 2015)
While the churches are emptying, other virtual religious places - as the religious websites - seem to be filling up. The researcher focusing on religion and internet or digital religion as an object of study must seek answers to a number of questions. Is computer-mediated religious communication a particular communication process whose object is what we conventionally call religion? Or is it a modern, independent form of religious expressiveness that finds its new-born status in the web and its particular language? To examine the questions above, and others, the book collects more empirical data, claiming that the Internet will have a specific or novel impact on how religious traditions are interpreted. The blurring of previous boundaries (offline/online, virtual/local, illegitimate/legitimate religion) is another theme common to all the contributions in this volume.